The Effect of Calcination Temperature on the Characteristics of CeO₂ Synthesized Using the Precipitation Method - Zidan Alfian Bahtiar; Tri Windarti; Dwi Hudiyanti (Jurnal Kimia Sains dan Aplikasi, 2024)
Cerium oxide (CeO2) was synthesized using the precipitation method at various calcination temperatures ranging from 500 to 700°C. Cerium(III) nitrate hexahydrate (Ce(NO)3.6H2O) was used as the precursor for cerium, while Cetyltrimethylammonium bromide (CTAB) acted as the morphology-directing agent. Characterization results indicated that pure CeO2 was obtained at all calcination temperature variations. Calcination temperature influences crystallinity, crystal size, and CeO2 crystal parameters. The crystallinity and crystal size of CeO2 increased with the rising calcination temperature, reaching values of 81.1–84.5% and 15.58–23.12 nm, respectively, along with larger crystal parameters as the temperature increased (a = 5.406–5.410 Å). Surface morphology showed irregular shapes of CeO2 particles, with decreasing sizes as the calcination temperature increased, ranging from 0.2-5.6 μm at 600°C to 0.12-2.9 μm at 700°C. The Ce/O ratio on the surface increased with the rising calcination temperature, reaching a range of 0.48–0.57. CeO2 obtained from calcination at 600°C exhibited the highest fluorescence emission intensity (λ= 496 nm), indicating the least oxygen vacancies presence. Therefore, for antioxidant and catalyst applications, it is preferable to calcinate CeO2 at 700°C.